2018
DOI: 10.1042/bsr20180400
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA SNHG5 regulates gefitinib resistance in lung adenocarcinoma cells by targetting miR-377/CASP1 axis

Abstract: Gefitinib resistance is one of the major obstacles for the treatment of lung adenocarcinoma (LAD). The present study aimed to investigate the effects of the long non-coding RNA (lncRNA), small nucleolar RNA host gene 5SNHG5 on gefitinib resistance in LAD and explore the underlying mechanisms. The quantitative real-time PCR (qRT-PCR) results showed that SNHG5 expression was significantly down-regulated in LAD patients with acquired gefitinib resistance and gefitinib resistant LAD cell lines. SNHG5 overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, the responsiveness of different HCC patients to gefitinib varies greatly and most patients even develop gefitinib resistance [ 60 ]. Multiple non-coding RNAs including miRNAs and lncRNAs have been reported to contribute to gefitinib resistance and sensitivity in NSCLC [ 61 63 ]. We speculate that gefitinib share the similar resistance mechanisms in HCC and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the responsiveness of different HCC patients to gefitinib varies greatly and most patients even develop gefitinib resistance [ 60 ]. Multiple non-coding RNAs including miRNAs and lncRNAs have been reported to contribute to gefitinib resistance and sensitivity in NSCLC [ 61 63 ]. We speculate that gefitinib share the similar resistance mechanisms in HCC and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are a type of ncRNA and play an important role in the tumorigenesis process. 9 lncRNA ANRIL is overexpressed in osteosarcoma and lung cancer; however, the role and biological mechanism of lncRNA ANRIL in glioma have not been fully understood. We found that there was an increased expression of lncRNA ANRIL in glioma tissue samples, positively correlated with grade.…”
Section: Discussionmentioning
confidence: 99%
“…It was formerly reported that SNHG5 is functionally related to many kinds of tumors, including chronic myeloid leukemia [ 8 ], gastric cancer [ 7 , 9 ], colorectal cancer [ 10 ], melanoma [ 11 ], and bladder cancer [ 12 ]. In addition, a recent document proclaimed that the overexpression of SNHG5 sensitized LAD cells to gefitinib treatment by interacting with miR-377 to modulate its downstream target, CASP1 [ 5 ]. However, the functions and molecular basis of SNHG5 in LAD cells and their correlation with LAD pathogenesis have not been further explored.…”
Section: Introductionmentioning
confidence: 99%